2015
DOI: 10.1021/jp512148b
|View full text |Cite
|
Sign up to set email alerts
|

Ab InitioMolecular Dynamics Simulation of Ethylene Reaction on Nickel (111) Surface

Abstract: We performed ab initio molecular dynamics (MD) simulations of ethylene molecules on the nickel (111) surface to understand the initial stage of graphene growth via a chemical vapor deposition process. Several hydrogen atoms are dissociated from ethylene molecules during the MD simulations in three different reaction mechanisms. It is seen that the ethylene molecules are easily chemisorbed on the nickel surface. This chemisorption contributes significantly to the dissociation reactions of ethylene molecules on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
0
23
1
1
Order By: Relevance
“…It should be noted that our previous study [42] has shown the adsorption energy of an ethylene molecule on the Ni(111) surface is calculated as 0.76 eV, which is only about half of the energy obtained in this study. This means that the reactivity of the Ni cluster is much higher than that of the Ni(111) surface.…”
Section: Adsorption Energy Of An Ethylene Molecule On the Niclustercontrasting
confidence: 66%
“…It should be noted that our previous study [42] has shown the adsorption energy of an ethylene molecule on the Ni(111) surface is calculated as 0.76 eV, which is only about half of the energy obtained in this study. This means that the reactivity of the Ni cluster is much higher than that of the Ni(111) surface.…”
Section: Adsorption Energy Of An Ethylene Molecule On the Niclustercontrasting
confidence: 66%
“…The simulation methodology basically follows our previous studies [29][30][31][32][33][34]. The projector augmented wave (PAW) method [38,39] is employed for the calculation of the electronic states, which is an all-electron electronic structure calculation method within the frozen-core approximation.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…On the other hand, we have closely discussed the dissociation of carbon source molecules on various catalytic metals based on the ab initio MD simulation [29][30][31][32][33], which takes into account both the chemical reaction with the accuracy of the ab initio calculation and the dynamics of atoms simultaneously, in order to discuss the initial stage of the CNT growth. Up to now, we have revealed the bond dissociation mechanism of ethane [29] and ethylene [30] on a nickel (1 1 1) surface, that of ethanol [31,32] and ethylene [33] on a nickel cluster, and that of methane and derivative fragment molecules on a copper (1 1 1) surface [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has to be mentioned, however, that the exchange reactions and the catalysis events over the formed active sites are all of a transient nature where the reactants interact and their properties change continually upon approaching the active site. These aspects are normally studied using molecular dynamics simulations at the first-principles level [75][76][77][78][79]. For the comparisons made herein, it will be assumed that the distribution of the Cu + ions at the exchange locations and the following Table 1.…”
Section: Resultsmentioning
confidence: 99%